Vehicle Tracking System Based on GPS and GSM Using Arduino - Sharma, Sonika; Ramudamu, Pushpa; Maya Tamang, Padam; Pradhan, Kiran; Pradhan, Arun (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The project involves the use of GPS and GSM technology wherein with the help of these modern concept and technology we aim to construct “modern vehicle tracking device”. This service enables the owner or the controllers of the service to locate the vehicle and also gather various information about the vehicle. The system includes the GPS module installed in the car to track and receive various information and pass it to owner with the help of GSM module.
Keywords: GPS; GSM; module; controller; device; track